The Influence of Technology Access, Socialization, and Social Preferences on the Use of the PLN Mobile Application at PT. PLN (Persero) Serui Customer Service Unit - A. Zulkifli; Hasniaty; Sadly Abdul Jabbar (GoodWill, 2025)
This study aims to determine: 1) the influence of technology access on the use of the PLN Mobile application at PT. PLN (Persero) Serui Customer Service Unit, 2) the influence of socialization on the use of the PLN Mobile application at PT. PLN (Persero) Serui Customer Service Unit, 3) the influence of social preferences on the use of the PLN Mobile application at PT. PLN (Persero) Serui Customer Service Unit, and 4) the influence of technology access, socialization, and social preferences on the use of the PLN Mobile application at PT. PLN (Persero) Serui Customer Service Unit. This study used a quantitative survey method to analyze the factors influencing the use of the PLN Mobile application at the Serui ULP. A sample of 100 respondents was selected using purposive sampling techniques and the Slovin formula. Data were collected through a Likert questionnaire, observation, and documentation, then analyzed using descriptive statistics, validity, reliability, normality, linearity, t-test, F-test, multiple linear regression, and coefficient of determination using SPSS. The results indicate that technology access, socialization, and social preference have a positive and significant influence, both individually and simultaneously, on the use of the PLN Mobile application at PT PLN (Persero) ULP Serui. Technology adaptation is the most dominant factor driving application utilization, followed by socialization and social preference. Based on these findings, it is recommended that PLN improve technology training, expand outreach campaigns, and develop community-based promotions and recommendation programs to strengthen sustainable application use.